2022
DOI: 10.1186/s12889-022-12967-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ perceptions of the health status of formerly detained immigrants

Abstract: Background In the past decade, the U.S. immigration detention system regularly detained more than 30,000 people per day; in 2019 prior to the pandemic, the daily detention population exceeded 52,000 people. Inhumane detention conditions have been documented by internal government watchdogs, and news media and human rights groups who have observed over-crowding, poor hygiene and sanitation and poor and delayed medical care, as well as verbal, physical and sexual abuse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…These facilities were operated by the US Department of Homeland Security (during the Trump administration this department was run by Kirstjen Nielson) (EO 13,768). These facilities experienced considerable growth in detained persons, accompanied by the rise in use of private prisons for detention, and they operate with inadequate numbers of support staff and medical staff (APHA, 2020 ; Hampton et al, 2022 ).…”
Section: Background and Context Of “Zero-tolerance”mentioning
confidence: 99%
See 1 more Smart Citation
“…These facilities were operated by the US Department of Homeland Security (during the Trump administration this department was run by Kirstjen Nielson) (EO 13,768). These facilities experienced considerable growth in detained persons, accompanied by the rise in use of private prisons for detention, and they operate with inadequate numbers of support staff and medical staff (APHA, 2020 ; Hampton et al, 2022 ).…”
Section: Background and Context Of “Zero-tolerance”mentioning
confidence: 99%
“…Men, women, and children were all detained and often separated from one another and held in different facilities (Hampton et al, 2022 ). Since children cannot be imprisoned with parents or family members, children were separated from parents and caregivers and separately placed into the federal custody of the US Department of Health and Human Services (Southern Poverty Law Center (SPLC), 2022 ).…”
Section: Background and Context Of “Zero-tolerance”mentioning
confidence: 99%
“…As the number of detained individuals has increased, civil and human rights organizations have raised concerns of substandard conditions in detention facilities across the country. Several published reports have highlighted overcrowded and unsanitary living conditions, physical and sexual abuse, inadequate nutrition, medical mismanagement, neglect, and abuse; leading to exacerbation of chronic medical conditions and/or development of new health conditions [ 2 , 3 , 8 , 9 ]. A study evaluating deaths of individuals in ICE detention facilities demonstrated that 71 individuals died while in ICE custody over a 7-year period, many of whom were young (mean age of 42.7 years at the time of death) with no or minor pre-existing conditions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluating deaths of individuals in ICE detention facilities demonstrated that 71 individuals died while in ICE custody over a 7-year period, many of whom were young (mean age of 42.7 years at the time of death) with no or minor pre-existing conditions [ 10 ]. Mental health care in ICE facilities has been of particular concern with suicide accounting for a number of deaths for at least 2 decades, and ongoing reports of the improper use of solitary confinement for those with mental health disorders (which in fact negatively affects physical and psychological health) [ 9 , 11 16 ]. Historically, ICE has engaged in other unsafe mental health care practices including detaining individuals with significant mental health conditions despite court ordered requirements for inpatient mental health treatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current research on the topic of migration and detention illustrates the wide-ranging issues migrants face while detained, including the increasing suicide rates of migrants, experiencing abuse and mistreatment while in detention, and the effects of forced family separation, particularly on migrant children's mental health ( Marquez et al., 2021 ; Becerra et al., 2022 ; Erfani et al., 2021 ; Hampton et al., 2022 ; Hampton et al., 2021 ; Wood, 2018 ). The COVID-19 pandemic further exemplified the risk of rapid transmission of communicable diseases while living in overcrowded facilities, indicating the need to consider alternative measures to detaining migrants to prevent outbreaks and avoid infection and death ( Casanova et al., 2021 ; Tosh et al., 2021 ; Lopez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%